2008
DOI: 10.1158/1541-7786.mcr-07-2161
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the Desmocollin 2 Gene Expression in Human Colon Cancer Cells Is Relieved by the Homeodomain Transcription Factors Cdx1 and Cdx2

Abstract: Desmosomes are intracellular junctions that provide strong cell-cell adhesion in epithelia and cardiac muscle. Their disruption causes several human diseases and contributes to the epithelial-to-mesenchymal transition observed in cancer. Desmocollin 2 (DSC2) is a cadherin superfamily member and a critical component of desmosomes found in intestinal epithelium. However, the mechanism regulating DSC2 gene expression in intestinal cells is not known. Cdx1 and Cdx2 are homeodomain transcription factors that regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 40 publications
2
38
1
Order By: Relevance
“…One challenge to understanding how Cdx2 regulates E-cadherin function has been the absence of an obvious transcriptional mechanism. Several cell-cell adhesion proteins have been identified as transcriptional targets for Cdx2 (12,23,39). Despite the suggestion from one early study that E-cadherin expression was regulated by Cdx2 (28), we found no evidence for this in studies of several colon cancer cell lines (11,12,25).…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…One challenge to understanding how Cdx2 regulates E-cadherin function has been the absence of an obvious transcriptional mechanism. Several cell-cell adhesion proteins have been identified as transcriptional targets for Cdx2 (12,23,39). Despite the suggestion from one early study that E-cadherin expression was regulated by Cdx2 (28), we found no evidence for this in studies of several colon cancer cell lines (11,12,25).…”
Section: Discussioncontrasting
confidence: 91%
“…The homeodomain transcription factor Cdx2 is required for intestinal differentiation and columnar morphogenesis (11)(12)(13)25). Cdx2 has been suggested to be a tumor suppressor (4,6) or to have tumor suppressor properties (16,17,19) in the colon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations